POLA PEMBINAAN TINGKAH LAKU WARGA BELAJAR PAKET A PASCA LITERASI / MELEK AKSARA - SANTOSO, SLAMET (Pendidikan Dasar, 2009)
Abstract: In Indonesia, the prominent aim of Kejar Paket A or Functional Literacy activity is Endeavour to literate of people from blind of reading and writing. The activity is implemented for along time to promote human development index. The reality, they had literate, but for the several years they illiterate again. So, in Indonesia illiteracy always present and the condition will deviate of the government activities in literacy. The aim of theoretical analysis approach is to give conceptual contribution so that the literacy activities are is not unless.